Effectiveness of massage therapy injury sports methods ali satia graha: experimental study against chronic ankle - Mahesvi, Hafiz; Sukarmin, Yustinus; Suhartini, Bernadeta; Graha, Ali Satia (Universitas Tanjungpura, 2023)
Background and Study Aim. The chronic ankle injury will interfere with the range of motion of the ankle joints, such as dorsiflexion, plantarflexion, inversion, and eversion. The motion of the ankle joint will be painful and limited. However, many methods are applied instead of curing the situation. Thus, the purpose of this study was to determine the effectiveness of massage therapy for sports injuries using the Ali Satia Graha method on pain and range of motion in the ankle.Material and Methods. This study used a Pre-experimental design with a one-group Pretest-Posttest Design. The subjects in this study were determined by the perposive sampling technique, so 15 male patients aged 25